Desain UI/UX Aplikasi MediSaku untuk Edukasi Obat Menggunakan Pendekatan User-Centered Design - Rasmila Rasmila; Muhammad Erlangga Fauzi; M Zakiansyah; Dzikri Thoriq Al Ariiq; Rachmat Adiaz Arrofi (Bulletin of Computer Science Research, 2025)
The rapid development of mobile device technology has encouraged the utilization of digital applications in various fields, including the provision of health information, particularly related to medications. Although many drug-education applications are currently available, a significant number of them still have complex user interfaces that make it difficult for general users to understand the information presented. This condition may lead to potential medication misuse. Therefore, this study aims to design the User Interface (UI) and User Experience (UX) of the MediSaku drug-education application based on Android that is simple, informative, and easy to use. The research method consists of preliminary study, user needs analysis, navigation structure and interface design, as well as the development of a high-fidelity prototype. The design process adopts a user-centered design approach and considers usability principles such as ease of use, consistency, and clarity of information. The result of this study is a high-fidelity prototype that includes several main pages, namely the splash screen, login, home, drug information, medication reminder, health articles, and user profile pages. Based on the conceptual design evaluation using heuristic principles, the MediSaku interface design is considered capable of facilitating users in accessing drug information and improving interaction comfort. This design is expected to serve as a foundation for the future implementation stage of the MediSaku application.